Control interno y su incidencia en la gestión administrativa de la empresa radio unika 93.5 fm del cantón Quevedo año 2023 - Zambrano Castillo, Cinthya Pamela (2025)
This project addressed the problem of the lack of adequate internal control in the administrative management of Radio Unika 93.5 FM. The study focused on evaluating the impact of internal control on the efficiency of the company's administrative processes, with the objective of proposing improvements to facilitate the fulfillment of its goals and objectives. A theoretical framework was established that contextualized the importance of internal control in business administration, highlighting its relevance for the optimization of resources and decision making. The research is significant because it allowed understanding how an efficient internal control system can improve